A literatura como fato social : instâncias e instituições que constroem o literário - Romais, Sandra Eleine (2006)
The current concept of literature is intrinsically related to the bourgeoisie revolution which is, in its turn, accountable for the development of the process in production, distribution and circulation of the literary construct and the necessary features for the spread and the acceptance of all artistic material. Literature materializes within the specific social practice of reading and writing, proper to a society inherently based on a bourgeois framework. A common idea of literature has been built on a network of factors that are interlaced into one another and which mould their concepts according to social and historical values. With these premises in mind, current research identifies the essential instances that construct literary texts and provide them proportion and aesthetic value that warrants them as literature. Among the instances of such a complex and comprising literary system, the following items have been analyzed: 1) the production and reception circuit, or rather, the constitution of the author and the reading public; 2) the circuit of the material production of texts, or rather, the evolution of printing techniques and new technologies; 3) the legislative and economical system which has been developed to regulate book selling, authors' and editors' rights; 4) discursive practices and the influence of such institutions as the Literary Academy and literary criticism and history in the elaboration of literature standards or models; 5) the educational system which trains the reading public or consumer and impart the values of the dominant class which affect the literary system. A bibliographical research was undertaken so that the above aims could be achieved. It has been foregrounded on sociological and Marxist bases in which the Brazilian historical and social course has been mainly underlined. Further, the production, distribution and consumption of the school textbook have been analyzed to verify the propriety of sociological studies within the dissertation. In current analysis the textbook has been understood to be a specific support within the perspective of the literary system. The manner the system is related to the textbook is investigated through practical examples and critical annotations. Current research is justified within the Brazilian context due to the relationships that ensue between literature and society. It contributes towards studies on the sociology of literature and, in a particular way, to research related to reader training. Results show that, whereas a wholly superficial literature is taught, limited and restricted to school standards and to an aesthetic power-maintaining group, literature as a social phenomenon has achieved surprising and overreaching heights. These dimensions are not restricted to artistic or aesthetic issues but, above all, comprise the social, political, economic, ideological and material environment. These relationships may not be discarded but should be understood precisely and critically so that a meaning may be provided (or attributed) to literature, its study and its reading within the context of the new paradigms of a post-modern society .